PELUANG DAN TANTANGAN USAHA MIKRO KECIL DAN MENENGAH DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN - Eka Dyah Setyaningsih (Universitas Bina Sarana Informatika, 2015)
Nowadays we are already in the ASEAN economic community section that should always be aware of the opportunities and challenges that occur especially in the case of SMEs (Small Medium Micro Enterprises), which plays a major role in the development of economic growth in Indonesia as a developing country in Indonesia. The performance of SMEs in Indonesia still must be monitored because there is still debate among academics about whether the Indonesian SMEs can compete in export markets or at least survive at home against the competition of imported goods that come from abroad. The study was conducted for our SMEs in order to take all the opportunities and overcome the challenges that occur either from internal and external environment in a company engaged in the SME industry. Monitoring of the SMEs was conducted through the presence of several strategies that lead to bottom-up which focus on the development of SMEs as one measure of economic growth. Research method is descriptive analytical study outlining strategies for SMEs as a way out alternatives in running the ASEAN economic community who are always ready to face any challenges and opportunities from both internal and external factors. Data collection through literature study secondary data sourced from literature journal reports and other official information that supports research on SMEs. Results from this study any measures or program that can compete in the market of regional (ASEAN) and maintaining or retaining domestic products in the domestic market share by increasing number of goods imported into the country. Therefore to support this it is necessary to empower back all the centers of SMEs that had developed with government support through a number of policies regarding the feasibility of SMEs. Keywords : Challenges Opportunities SME Strategy, ASEAN Economic Community